Group Guidance with Problem-Solving Techniques to Prevent Suicidal Ideation - Asep Solikin; Tiara Tiara; Karyanti Karyanti (Suluh: Jurnal Bimbingan dan Konseling, 2024)
Aim: determine the differences in the level of suicidal ideation before and after the implementation of group guidance on students at Muhammadiyah Middle School, Palangkaraya, (2) determine the effectiveness of group guidance in preventing suicidal ideation in students at Muhammadiyah Middle School, Palangkaraya. Method: The population in this study were all students of class VIII of SMP Muhammadiyah Palangka Raya, Central Kalimantan, totaling 71 students. The sample of this study consisted of 9 students out of 21 students of class VIII-C. Sampling was determined by the purposive sampling technique. Result and Discussions: The results of the study showed that: (1) before being given group guidance services, most of the students in class VIII-C, namely 9 students, experienced suicidal ideation with a moderate category. After being given group guidance services with the Problem Solving technique, most of the students, namely 5 students with a low category, and 4 students with a moderate category. The total Pre-test score was 587 and the Post-test score was 437, the total score difference was 150. This means that many changes occurred after the provision of group guidance services by the researcher; (2) the results of the hypothesis test calculation using SPSS 25 software on the paired sample T-Test method showed that the significance value obtained was 0.001. This shows that the Sig value <0.05, which means that there is an influence of Problem-Solving to prevent suicidal ideation in class VIII.C students of SMP Muhammadiyah Palangka Raya.